Multifactor interactions and the air traffic controller: The interaction of situation awareness and workload in association with automation. Issue 19 (2016) - Edwards, T.; Homola, J.; Mercer, J.; Claudatos, L.
Abstract: Air traffic controllers (ATCOs) must maintain a consistently high level of human performance in order to maintain flight safety and efficiency. In current control environments, performance-influencing factors such as workload, fatigue and situation awareness can co-occur and interact to affect performance. However, multifactor influences and the association with performance are under-researched. This study utilized a high fidelity human in the loop en-route air traffic control simulation to investigate the relationship between workload, situation awareness and ATCO performance. The current study aimed to replicate Edwards, Sharples, Wilson and Kirwan's (2012) previous research, and extend the study by using a ex-controllers as participants, and comparing multifactor relationships across four levels of automation. Results suggest that workload and situation awareness may interact to produce a compound impact on controller performance. In addition, the effect of the interaction on performance may be dependent on the context and level of automation. Findings have implications for human-automation teaming in air traffic control, and the potential prediction, and therefore support, of ATCO performance.